Pengaruh Penerapan Pembelajaran Berbasis Masalah dengan Pendekatan Konstektual terhadap Hasil dan Motivasi Belajar Matematika Siswa Kelas X SMA Negeri I Inanwatan - Rosa Sapulette; Disabella Dayera (Journal on Education, 2023)
The study is pre-experimental research, which aims at examining the influence of the implementation of problem- based learning using contextual approach toward the result and learning motivation of student at SMAN 1 Inanwatan. The populations of the study were all of grade X students at SMAN 1 Inanwatan. The sample was grade X A as the experiment class chosen by employing cluster random sampling technigue. Based the result of Mathematics learning before implementing problem- based learning using contextual approach , it is discovered that the mean score is 35,2 and standard of deviation 15,51, the level of completeness classically is 100% which is in Incomplete category : whereas the learning result after implementing problem- based learning using contextual approach is 92% which is in complete cattegory. The result of hypotesis at the level of significance with t-test indicates that there is influence and improvement of learning result and learning motivation in Mathematics subject of students after learning implementing problem-based learning using contextual approach at SMAN I Inanwatan.